Variational Calculations of Highly Excited Rovibrational States for the Ground Electronic State of N20 - Noh Daudl, Mohammad; Baling-Kurti, Gabriel G. (Malaysian Journal of Science, 2017)
Variational calculations are presented for highly excited vibrational bound states of N20 using a newly constructed ab initio multireference configuration interaction potential energy surface. The calculations are performed using a Jacobi coordinate system. The vibrational energies are compared with experimental data and the sources of the discrepancy between them are discussed.